A Prospective Comparative Study between Implantable Phakic Intraocular Contact Lens and Implantable Collamer Lens in Treatment of Myopia in Adults - Mahmoud Rateb; Ahmed A.M. Gad; Dalia Tohamy; Mohamed Nagy Elmohamady (Journal of Ophthalmology)
Purpose. To compare implantable collamer lenses (ICLs) and acrylic implantable phakic contact lenses (IPCLs) in the treatment of myopia in adults, as regards refractive outcome and adverse effects. Methods. Prospective, randomized comparative study with phakic intraocular lenses (IOLs) was carried out for treatment of myopia. Patients were randomized into two groups: one for ICL and the other for IPCL. Preoperative assessments included a full examination, pentacam, endothelial cell count, and biometry. We compared the adverse effects and refractive outcomes between both groups. The study was registered in clinical trials and the registration number is NCT04624035. Results. Sixty eyes of sixty patients (28 in the ICL group and 32 in the IPCL group) with a follow-up period of 12 months. The mean preoperative spherical equivalent was −12.7 ± 3.4 D and −13.6 ± 4.4 D in the ICL and IPCL groups, respectively (P=0.37). The mean postoperative spherical equivalent value was ±0.4 ± 0.2 D and ±0.6 ± 0.1 D in the ICL and IPCL groups, respectively. Uncorrected visual acuity (UCVA) has improved from 1.3 ± 0.06 to 0.15 ± 0.02 Log MAR in the ICL group (P<0.001) and from 1.3 ± 0.02 to 0.15 ± 0.01 Log MAR in the IPCL group (P<0.001). The mean endothelial cell count was reduced by 3.3% in the IPCL group and by 3.2% in the IPCL group. Conclusion. Both ICL and IPCL are effective methods to correct high myopia in adults with no statistically significant differences between the two lenses as regarding adverse effects.